PREDICTORS OF PURCHASE DECISION ON HALAL LIPSTICK PRODUCT IN BANDUNG - Damaianti, Indriana; Shafi, Sujana; Afiany, Fitri; Devi, Wiara (Faculty of Economics and Business, University of Pasundan, 2023)
The halal cosmetics industry presents potential trends and contributes significantly to the economy. Wardah, an Indonesian halal cosmetic brand, was the first to obtain halal certification. While lipstick remains a popular product, the sales index of Wardah lipstick has experienced a decline. This study focuses on how brand image, product quality, and word-of-mouth (WOM) influence purchase decisions. The method employed is descriptive verification, utilizing multiple linear regression analysis processed with SPSS 26. The unit of analysis is individuals, specifically working women, with several hundred respondents. The results indicate that both brand image and product quality have a significant impact on purchase decisions, while WOM does not significantly influence these decisions. Increased purchase decisions are essential for a business to grow and maintain sustainability.